Hirschsprung disease: a developmental disorder of the enteric nervous system. (24th April 2012) - McKeown, Sonja J.; Stamp, Lincon; Hao, Marlene M.; Young, Heather M.
Abstract Hirschsprung disease (HSCR), which is also called congenital megacolon or intestinal aganglionosis, is characterized by an absence of enteric (intrinsic) neurons from variable lengths of the most distal bowel. Because enteric neurons are essential for propulsive intestinal motility, infants with HSCR suffer from severe constipation and have a distended abdomen. Currently the only treatment is surgical removal of the affected bowel. HSCR has an incidence of around 1:5, 000 live births, with a 4:1 male:female gender bias. Most enteric neurons arise from neural crest cells that emigrate from the caudal hindbrain and then migrate caudally along the entire gut. The absence of enteric neurons from variable lengths of the bowel in HSCR results from a failure of neural crest‐derived cells to colonize the affected gut regions. HSCR is therefore regarded as a neurocristopathy. HSCR is a multigenic disorder and has become a paradigm for understanding complex factorial disorders. The major HSCR susceptibility gene is RET. The penetrance of several mutations in HSCR susceptibility genes is sex‐dependent. HSCR can occur as an isolated disorder or as part of syndromes; for example, Type IV Waardenburg syndrome is characterized by deafness and pigmentation defects as well as intestinal aganglionosis. Studies using animal models have shown that HSCR genes regulate multiple processes including survival, proliferation, differentiation, and migration. Research into HSCR and the development of enteric neurons is an excellent example of the cross fertilization of ideas that can occur between human molecular geneticists and researchers using animal models. WIREs Dev Biol 2013, 2:113–129. doi: 10.1002/wdev.57 For further resources related to this article, please visit the WIREs website.